2017
DOI: 10.17305/bjbms.2017.2039
|View full text |Cite
|
Sign up to set email alerts
|

Follicular morphological characteristics may be associated with invasion in follicular thyroid neoplasms with papillary-like nuclear features

Abstract: The newly proposed nomenclature and diagnostic criteria for encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC), the noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP), could improve the consistency and accuracy of diagnosing this entity. Diagnosis of NIFTP requires evaluation of the complete tumor border or capsule. The presence of tumor invasion in follicular thyroid neoplasms with papillary-like nuclear features has been recently discussed by many author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The size of the tumor does not constitute a criterion for the diagnosis of NIFTP (Nikiforov et al 2018), although some cases require greater care and time-consuming evaluation to ensure the absence of excluding findings. Reviewing 250 patients with subcentimeter NIFTP from nine studies (Thompson 2016, Can et al 2017, Hahn et al 2017, Kwon et al 2017, Johnson & Sadow 2018, Mainthia et al 2018, Rosario 2018c, Shafique et al 2018, Xu et al 2018, without associated PTC, we found only two patients with micrometastases <2 mm in a single lymph node in the central compartment, none with distant metastases and no case of recurrence. In addition, reviewing 265 patients with NIFTP ≥4 cm (Thompson 2016, Golding et al 2017, Kwon et al 2017, Rosario 2017b, Xu et al 2017a, Chereau et al 2019, Kim et al 2018b, Mainthia et al 2018, Parente et al 2018, excluding cases with associated PTC, we did not identify any patients with lymph node metastases (LNM), only one with pulmonary metastases and no case of recurrence.…”
Section: Diagnosis Of Niftpmentioning
confidence: 88%
“…The size of the tumor does not constitute a criterion for the diagnosis of NIFTP (Nikiforov et al 2018), although some cases require greater care and time-consuming evaluation to ensure the absence of excluding findings. Reviewing 250 patients with subcentimeter NIFTP from nine studies (Thompson 2016, Can et al 2017, Hahn et al 2017, Kwon et al 2017, Johnson & Sadow 2018, Mainthia et al 2018, Rosario 2018c, Shafique et al 2018, Xu et al 2018, without associated PTC, we found only two patients with micrometastases <2 mm in a single lymph node in the central compartment, none with distant metastases and no case of recurrence. In addition, reviewing 265 patients with NIFTP ≥4 cm (Thompson 2016, Golding et al 2017, Kwon et al 2017, Rosario 2017b, Xu et al 2017a, Chereau et al 2019, Kim et al 2018b, Mainthia et al 2018, Parente et al 2018, excluding cases with associated PTC, we did not identify any patients with lymph node metastases (LNM), only one with pulmonary metastases and no case of recurrence.…”
Section: Diagnosis Of Niftpmentioning
confidence: 88%
“…One of these subjects had under gone in complete excision and non invasive nature of tumor was questionable in other patient. In general, data suggest that the rate of negative result is very low in the absence of invasion of this lesion [12][13][14][15][16][17][18].…”
Section: Editorialmentioning
confidence: 84%